2008
DOI: 10.1111/j.1365-2249.2008.03602.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune tolerance induction to enzyme-replacement therapy by co-administration of short-term, low-dose methotrexate in a murine Pompe disease model

Abstract: SummaryClinical investigations of recombinant human acid a-glucosidase for the treatment of Pompe disease often reveal the appearance of therapy-specific antibodies. These antibodies could potentially interfere with recombinant human acid a-glucosidase efficacy and induce immunological consequences. Several immunosuppressive agents, including methotrexate, mycophenolate mofetil and cyclosporin A with azathioprine, were evaluated for their potential to induce immune tolerance to recombinant human acid a-glucosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 38 publications
2
72
0
1
Order By: Relevance
“…Strategies to induce tolerance include conjugating antigen to splenocytes [8], immature dendritic cells (DC) [9,10], or synthetic microparticles [11,12], oral tolerance [13], gene therapy [14] or co-treatment with immunosuppressive drugs, such as methotrexate [15]. Recently, it has been reported that systemic co-administration of rapamycin, a immunosuppressant drug commonly used to prevent transplant rejection, prevented immune response and induced tolerance to FIX and FVIII in mouse models of hemophilia A and B, respectively [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to induce tolerance include conjugating antigen to splenocytes [8], immature dendritic cells (DC) [9,10], or synthetic microparticles [11,12], oral tolerance [13], gene therapy [14] or co-treatment with immunosuppressive drugs, such as methotrexate [15]. Recently, it has been reported that systemic co-administration of rapamycin, a immunosuppressant drug commonly used to prevent transplant rejection, prevented immune response and induced tolerance to FIX and FVIII in mouse models of hemophilia A and B, respectively [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Diphenhydramine (15 mg/kg) was intraperitoneally injected 10-15 min prior to each enzyme administration to prevent anaphylactic reactions [23].…”
Section: Treatment Of Young Adult Gaa-ko Mice With Fabgaamentioning
confidence: 99%
“…The mechanism by which methotrexate exerts these effects is presumed to be through killing proliferating cells by inhibiting dihydrofolate reductase and inducing immunosuppression (9,10). Our laboratory has also demonstrated that methotrexate can significantly reduce inflammatory responses against protein therapeutics (11,12). In particular, we have shown that methotrexate significantly decreases the development of antidrug Abs, however, not through immunosuppression but rather through the induction of immune tolerance because only a few short courses of methotrexate can significantly reduce Abs that develop in mice against the enzyme replacement therapies, Fabrazyme and Myozyme, for extended periods of time (11,12).…”
mentioning
confidence: 92%
“…For these studies, methotrexate was tested as an immune tolerance inducing agent to mATG and was administered in a similar regimen to that used to tolerize Myozyme and Fabrazyme (11,12). Administration of 5 mg/kg methotrexate within 15 min of as well as 24 and 48 h following the initial three mATG treatments, significantly reduced anti-drug Ab titers by 69% through 6 mo of monthly mATG administration (Fig.…”
Section: Serum Alloantibody Levelsmentioning
confidence: 99%
See 1 more Smart Citation